Fits of Political Religion: Stalking Infidelity and the Politics of Moral Reform in Antebellum America. - Schlereth, Eric R. (Early American Studies, An Interdisciplinary Journal)
In the late 1820s evangelical Protestants created Bible, tract, and missionary societies and renewed efforts to suspend Sunday mail delivery. Deistic free enquirers responded by forming their own societies, holding public debates, and publishing newspapers and pamphlets. Evangelical reformers outnumbered free enquirers, a difference far from evident to contemporary observers, who believed instead that "political religion" and "stalking infidelity" were equally powerful cultural developments. By centering on the collective assumptions, misapprehensions, and fears that shaped ideas and motivated actions of self-avowed free enquirers as well as advocates of Christian moral reform, this article argues that the central features of antebellum American religion and politics were shaped by contests over the presence of "political religion" and "stalking infidelity" in American society. Particular attention is given to free enquiry as a lens into the broader ways that "infidelity" and organized moral reform were competitive and intertwined political positions that eventually shaped the religious and moral texture of the Second Party System. Disputes between free enquirers and moral reformers took place within a context shaped by differing conceptions of citizenship, changing understandings of civil society, and a renewed cultural interest in the memory and meaning of the American Revolution. This article pays special attention to the opportunities provided in an urban context for print circulation, sociability, and religious controversy.